2020
DOI: 10.3390/cancers12040848
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and Genomic Heterogeneity in the Evolution and Progression of Breast Cancer

Abstract: Breast cancer is a remarkably complex and diverse disease. Subtyping based on morphology, genomics, biomarkers and/or clinical parameters seeks to stratify optimal approaches for management, but it is clear that every breast cancer is fundamentally unique. Intra-tumour heterogeneity adds further complexity and impacts a patient’s response to neoadjuvant or adjuvant therapy. Here, we review some established and more recent evidence related to the complex nature of breast cancer evolution. We describe morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 162 publications
(241 reference statements)
0
11
0
Order By: Relevance
“…Compelling evidence has suggested that intra- and inter-tumoral heterogeneity should be taken into careful consideration for an adequate selection of patients [ 2 , 132 ]. In this respect, liquid biopsy allowing the identification of circulating tumor cells (CTCs) in the peripheral blood and the sequencing of the tumor DNA extracted from CTCs would provide the genetic profile of the malignancy [ 133 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Compelling evidence has suggested that intra- and inter-tumoral heterogeneity should be taken into careful consideration for an adequate selection of patients [ 2 , 132 ]. In this respect, liquid biopsy allowing the identification of circulating tumor cells (CTCs) in the peripheral blood and the sequencing of the tumor DNA extracted from CTCs would provide the genetic profile of the malignancy [ 133 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Breast cancer (BC) is a heterogeneous disease with at least twenty histological subtypes of invasive breast cancer, based on growth patterns and morphology, and three biological subtypes, characterized by the expression of estrogen receptor (ER) and progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2), or the lack of all three receptors (triple-negative BC (TNBC)). The “omics“ technologies have confirmed and further stratified molecular heterogeneity of this disease into biologically and clinically meaningful subtypes, including at least six intrinsic subtypes (normal, claudin-low, luminal A and B, HER2-enriched, and basal) and four TNBC molecular subtypes (basal-like 1 and 2, mesenchymal, and luminal androgen receptor) [ 1 ]. TNBC is among the most aggressive and early metastasizing tumors [ 2 , 3 ], and the poor treatment response and early therapeutic escape from conventional treatments eventually leads to aggressive metastatic disease.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent mutated genes in ERα-positive breast cancers are PIK3CA, GATA3, MAP3K1, KMT2C and TP53. Mutation of CDH1 (encoding E-cadherin) or loss of alleles are common in the lobular subtype (reviewed in [15,255]). In contrast, ESR1 mutations are rare (less < 1%) in primary ERα-positive breast cancers [256] but between 20 and 40% of ESR1 mutations are observed in metastatic breast cancer and influence response to hormone therapy (reviewed in [256][257][258][259][260]).…”
Section: Mutations Of Esr1 In Human Breast Tumorsmentioning
confidence: 99%